2003
DOI: 10.1038/sj.bjc.6601382
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of irinotecan plus chronomodulated oxaliplatin, 5-fluorouracil and folinic acid in advanced colorectal cancer patients

Abstract: The combination of irinotecan (CPT-11), oxaliplatin (L-OHP), 5-fluorouracil (5-FU) and folinic acid (FA) is one of the possibilities to overcome chemoresistance in advanced colorectal cancer (ACRC) patients. The aim of this study was to determine the tolerability and activity of CPT-11 plus chronomodulated infusion of L-OHP, 5-FU and FA in ACRC patients. A total of 35 patients (91% pretreated, 77% with CPT-11, 54% with L-OHP, 42% with both) were treated every 3 weeks with CPT-11, 180 mg m À2 day 1 i.v., plus L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 17 publications
(26 reference statements)
1
12
0
Order By: Relevance
“…That regimen produced an objective response rate of 22.9% and disease stabilization in 42.9% of the patients. However, only 42% of the patients had previously received irinotecan, 5-FU/LV, and oxaliplatin; a stabilization rate of 53.3% and no objective responses were obtained in this patient subset [35]. In our study, all the patients had previously progressed on 5-FU/LV, irinotecan, and oxaliplatin.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…That regimen produced an objective response rate of 22.9% and disease stabilization in 42.9% of the patients. However, only 42% of the patients had previously received irinotecan, 5-FU/LV, and oxaliplatin; a stabilization rate of 53.3% and no objective responses were obtained in this patient subset [35]. In our study, all the patients had previously progressed on 5-FU/LV, irinotecan, and oxaliplatin.…”
Section: Discussionmentioning
confidence: 89%
“…The association of all four drugs [7,30] and the chronomodulation of their delivery most likely accounted for this tumor control in such a patient population. In a phase II study involving 35 MCRC patients, chronomodulated 5-FU/LV and oxaliplatin were combined with a 1-hour morning infusion of irinotecan [35]. That regimen produced an objective response rate of 22.9% and disease stabilization in 42.9% of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have evaluated the combination of FU with l-OHP and/or IRI administered as chronomodulated infusion. These trials also reported interesting response rates and optimal toxicity profiles, but raised questions about the feasibility of chronomodulated chemotherapy (Garufi et al, 2003). However, the analysis of seven phase III trials in advanced CRC suggested that exposure to all three drugs, regardless of their sequence, is a key element able to extend the overall survival of patients to 18 -21 months (Grothey et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, this is the reason why we are presently developing more elaborate models of cell proliferation, for healthy or tumour tissues. These new models take into account several physiological events in the cell cycle, which are targeted by anti-cancer drugs (Bekkal-Brikci et al 2008;Clairambault 2008), so as to deal jointly with the circadian regulation of cell cycle determinants and therapeutic optimization of control flows for several drugs, such as 5-FU, oxaliplatin and irinotecan, which are used as triplets for treating colorectal cancer (Garufi et al 2003;Falcone et al 2007). …”
Section: Identification Of Optimal Circadian Delivery Schedules Of Oxmentioning
confidence: 99%